CULTURAL ECONOMICS STUDY ON SONOK COW PRICE DETERMINATION IN MADURA - Fuad Hasan; Slamet Widodo; Karisma Trinika Febriyanti (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Cultural products have characteristics that cannot be explained by neo classical economic theory like other functional products. The price of cultural goods is not only determined by economic activity and the resources used but also by social values. The sonok cattle is a cultural item that is unique compared to other cultural goods. This uniqueness is an attraction for study compared to other cultural goods. This study aims to determine the non-economic factors that affect the price of sonok cattle in Madura. The research was conducted in the Sonok cattle development area in the Pamekasan Regency area. Primary data were collected using structured interviews toward 43 respondents who had bought sonok cattle in the last two years and one key informant, namely the head of the sonok cattle association. The data were analyzed using multiple linear regression. The results of the analysis showed that price had a positive effect toward the reputation of sonok cattle and the social status expected by buyers. Sonok cattle that have a high reputation based on the number of contest champion statuses, the higher the price of the cow. The implication of the research results for sonok cattle owners is to increase participation in contests to increase the chances of obtaining champion status so that the cows have a high reputation which will ultimately increase prices.